Tuber quality enhancement via grafting potato onto a wooden goji rootstock through vitalizing multi-pathways - Elsadek, Mohamed A (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.